Green Education in Healthcare: What Does It Mean? Findings from a Literature Review - Cucchiaro, Michela; Moreale, Renzo; Moreal, Chiara; Dentice, Sara; Magro, Gaia; Dussi, Gaia; Palese, Alvisa; Chiappinotto, Stefania (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Sustainability is an emerging issue in many contexts, including education: the targets of the World Health Organization's Agenda 2030 have pushed for sustainable development of health systems, including training and digitalization. The aim of the study was to identify green and sustainable strategies in different health education settings, in particular in the digital field, through a literature review. Sustainable healthcare was defined as the evaluation of resources, recycling strategies and taking care of nature, while green education focuses on the skills needed to carry out consciously sustainable actions. Some identified digital strategies were simulations, online lectures and tests. There is an urgent need to address the effects of the climate crisis and promote a sustainable health model starting from professionals who have a crucial role.